Book Review: Infrastructure for Asian Connectivity - Sandee, Henry (Taylor and Francis, 2014)
This article reviews the book Infrastructure for Asian Connectivity edited by Bhattacharyay, Kawai and Nag (2012). This book is the second publication coordinated by the ADB and the ADB Institute focusing on infrastructure and connectivity in Asian countries. This book looks at regional (across border) infrastructure that is needed to facilitate growth and development through better connectivity and integration among countries.